Revitalisasi Taman Tepian Slamet Riyadi Menjadi Wadah Pariwisata Tepi Sungai Dengan Rekreasi Air Perahu Dayung - Sari, Dharwati P.; Azizah, Anisah; Prananta, Nayla Alifah (Universitas Mulawarman, 2025)
Developing a waterfront area requires careful planning, considering local potential, site characteristics, and community needs. This study aims to redesign Taman Tepian Slamet Riyadi in Samarinda into a tourism destination based on water recreation while promoting local cultural identity. The core concept includes the development of a boat dock for rowing boat activities, green open spaces, playgrounds, an amphitheater, a venue, and a riverside restaurant. A key feature of the site is the Jukung Barunai monument, which symbolizes the cultural heritage of river life. The Jukut restaurant offers local cuisine in a natural riverside setting. Planning methods involved on-site observation, SWOT analysis, and spatial zoning approaches. The result is an integrated design that balances aesthetics, environmental sustainability, and social interaction. In addition to supporting tourism activities, this project is expected to open new economic opportunities and raise public awareness of the importance of preserving the Mahakam River ecosystem.